Motivational determinants of physical education grades and the intention to practice sport in the future - Cid, Luis (2019)
Self-Determination Theory (SDT) is amongst motivational frameworks the most popular and contemporary approach to human motivation, being applied in the last decades in several domains, including sport, exercise and physical education (PE). Additionally, Achievement Goal Theory (AGT) has presented evidence of how contextual factors may influence student's behavior in this particular context. The main purpose of this study was to analyze the motivational climate created by the teacher in the classroom, students' satisfaction of Basic Psychological Needs (BPN), and how their behavioral regulation could explain PE grades and intention to practice sports in the future.